Delivering Difficult News and Improving Family Communication: Simulation for Neonatal-Perinatal Fellows - Danielle Janice-Woods Reed; Jotishna Sharma (Association of American Medical Colleges, 2016)
Abstract Introduction This 3-hour simulation module provides a safe situation for neonatal-perinatal fellows to learn communication techniques and develop skills for delivering difficult news to patients' families. These skills are critical for a practicing neonatologist in an academic or private-practice setting yet are often underrepresented in the educational content of training programs. This module is intended for fellows who have had basic communication skills instruction, as well as interactions with parents as part of their pediatric residency training. Methods The fellows practice delivering difficult news by interacting with standardized parents in scenarios designed for one to three learners at a time. Each scenario runs for approximately 10 to 15 minutes and is followed by a 25- to 30-minute debriefing. Those not participating in the scenario view the simulation in real-time video broadcast from another room so they can learn from the scenario and participate in the debriefing. The module also includes 10 to 15 minutes for discussion of literature. This publication includes an introductory slide presentation and a comprehensive compilation of communication recommendations from attending neonatologists. Also included are scripts for the standardized parents, background information for learners, guidelines and suggestions for discussion during the debriefing, and an evaluation form. Results This module has been incorporated into the yearly simulation curriculum for our neonatal-perinatal fellowship. After completing the module, fellows have reported feeling more comfortable with delivering difficult news. The average score in fellows' comfort level for having these conversations rose from 5.8 to 7.5 on a 10-point scale. Discussion This module was designed for use in a perinatal-neonatal fellowship training program, but it could be used in all pediatric residencies, as well as for support staff training (social work, nursing, chaplaincy) with the use of a confederate physician.